Molecular genetic mechanisms of eosinophil activation in aspirin-exacerbated respiratory disease - Purevsuren Losol (The Graduate School, Ajou University, 2013)
Background and Objective: Eosinophilic airway inflammation is a common pattern in various phenotypes of asthma. Persistent eosinophil activation finding in both upper and lower airway mucosa is a central feature of aspirin-exacerbated respiratory disease (AERD). As interleukin (IL)-5 mediated signal transduction has been shown to participate in survival and effector function of eosinophils, IL-5 and its specific receptor subunit IL-5 receptor alpha (IL5RA) have been attractive targets for eosinophil associated disorders. Furthermore, it has been reported that platelets interacted with eosinophils involve in both asthma and AERD patients, in which both cells could express purinergic receptor P2Y12. Considering that elevated eosinophil infiltration constitutes a major characteristic feature of asthma and AERD, we hypothesize that activation of eosinophils via dysregulation of IL5, IL5RA and P2RY12 genes may play an important role in the pathogenesis of asthma and AERD. We purposed to identify a potential association of IL5, IL5RA and P2RY12 genetic polymorphisms in the susceptibility to asthma and AERD in a Korean population. Materials and Methods: The two study groups, 310 adult asthmatics and 160 normal controls (NC), were enrolled at Ajou University Medical Center, Suwon, South Korea. IL5 polymorphisms, –746A>G and 4499T>G, were genotyped using the primer-extension method and the SNaPshot ddNTP primer extension kit. Serum total and specific IgE to staphylococcal enterotoxin A (SEA) and B (SEB) were measured by ImmunoCAP system. In IL5RA study, three study groups, 139 patients with AERD, 171 patients with aspirin-tolerant asthma (ATA) and 160 NC were recruited. IL5RA polymorphisms (-5993G>A, -5567C>G and -5091G>A) were genotyped using the primer-extension method and the SNaPshot ddNTP primer extension kit. The functional activity of these polymorphisms were assessed by luciferase reporter assay and electrophoretic mobility shift assay (EMSA). Finally, P2Y12 receptor gene (P2RY12) polymorphisms (-46437C>A, 742T>C and 18C>T) were genotyped in 218 AERD patients, 330 ATA patients and 183 NC by TaqMan allelic discrimination assay. For the functional study, platelet-rich plasma was isolated from AERD, ATA and NC subjects to measure levels of soluble P-selectin by ELISA, and expression of P-selectin and P2Y12 on platelets were measured during aspirin challenges using a flow cytometry. Eosinophil cationic protein (ECP) level in nasal lavage fluid (NLF) from AERD and ATA patients was measured after nasal provocation test with lysine-aspirin. Results: There were no significant differences in genotype, haplotype and allele frequencies of IL5 polymorphisms between the two groups. Asthmatics carrying the AG/GG genotype at –746A>G had a significantly higher prevalence of serum specific IgE to SEA (p=0.008), higher total IgE levels (p=0.014), and lower PC20 methacholine levels (p=0.001) than those with AA. The three common haplotypes for two polymorphisms were constructed: HT1 [AT], HT2 [GT] and HT3 [GG]. There was no significant difference between asthmatics and NC. In association of IL5RA polymorphisms, there were no significant differences in the genotype and allele frequencies of the three polymorphisms among the three groups. The five common haplotypes for three polymorphisms were constructed: HT1 [GGG], HT2 [ACA], HT3 [ACG], HT4 [GCG] and HT5 [AGG]. The HT5 [AGG] was significantly higher in dominant model in the AERD patients compared to the NC (p=0.043). AERD patients carrying the AA genotype at -5993G>A had a significantly higher prevalence of serum specific IgE to SEA (p=0.008) than those with the GG/GA genotypes. In vitro, the -5993A allele had a higher promoter activity compared to the -5993G allele in HMC-1 (p=0.030) and HL-60 (p=0.013) cells. In EMSA, a -5993A probe produced a specific shifted band than the -5993G had. The association studies of P2RY12 polymorphisms showed no significant differences in genotype and allele frequencies among study groups. The three common haplotypes were constructed for three polymorphisms: HT1 [CTC], HT2 [CTT] and HT3 [ACC]. The HT3 [ACC] frequency was significantly lower in patients with AERD compared to ATA in codominant (p=0.011) and dominant (p=0.005) models. The AERD patients with 742TC/CC genotypes had a greater fall of FEV1 (p=0.044) and higher ECP level in NLF (p=0.047) than those with the 742TT genotypes after lysine-aspirin challenges. AERD patients with 18CT/TT genotypes had a higher expression of P2Y12 on platelets than those with the 18CC genotype (p=0.025), and these expression levels that collected after aspirin challenges were significantly different between two groups (p=0.022). Conclusion: These findings suggest that the IL5 promoter polymorphism at –746A>G and IL5RA polymorphism at -5993G>A may contribute to eosinophil activation along with specific IgE responses to SEA in asthma and AERD patients. P2RY12 genetic polymorphisms at 742T>C and 18C>T could contribute to eosinophil and platelet activation in AERD patients.
학위논문(박사)----아주대학교 일반대학원 :의학과,2013. 8